##### Ad

related to: K

2

**k**x² - 12x + (**k**+7) = 0 Solve for**k**b² - 4ac = 0 (b = -12, a = 2**k**and c =**k**...8 ..........-**k**² - 7**k**+ 18 = 0 ..........**k**² + 7**k**- 18 = 0 ........ (**k**- 2) (**k**+ 9) = 0 ......**k**- 2 = 0..........................**k**+ 9 = 0**k**- 2 + 2 = 0 + 2...4 Answers · Science & Mathematics · 12/09/2010

Sources of Vitamin

**K**Vitamin**K**is found chiefly in leafy green ...of vitamin**K**.[7]. Some vegetable oils, notably soybean, contain vitamin**K**, but at levels that would require relatively large caloric consumption to meet the...9 Answers · Food & Drink · 07/03/2009

If

**k**-2 divides 2**k**,**k**-2 ≠ 0, then there is an integer i such that 2**k**= (**k**-2)i Solving for**k**gives... of i less than or equal to 1 that produce**k**≥ 3. Therefore the only ...1 Answers · Science & Mathematics · 20/03/2009

∫(x = 0 to 1) x^

**k**ln x dx = ∫(∞ to 0) (e^w)^**k*** w * (e^w...;==> x = e^w = -∫(w = 0 to ∞) we^((**k**+1)w) dw = -∫(w = 0 to ∞) we^((**k**+1)w) dw...1)t))] = (-1/(**k**+1)^2) * [1 + lim(t→∞) -e^((**k**+1)t)] = (-1/(**k**+1)^2) * (1 + 0), since**k**+1...3 Answers · Science & Mathematics · 10/06/2015

(2

**k**+1) * (2k) * (2k-1) * ... * (**k**+2) * (**k**+1) / 2 = (2k+1) ***k*** [(2k-1) * ... * (**k**+2) * (**k**+1)] In...ellipsis notation from becoming ambiguous. (Otherwise the**k**factor is out of sequence and makes that notation unclear.)1 Answers · Science & Mathematics · 18/07/2011

**K**-9/27 =7/9 Step 1, Multiply 27 to the whole entire problem. 27(**K**-9/27 =7/9) 27K - 9 = 21 Step 2, Add 9 and Divide...2 Answers · Science & Mathematics · 05/05/2012

C=

**K**(Rr/R-r) Divide both sides by**K**: C...r): (R-r)(C/**K**) = Rr Distribute C/**K**: CR/**K**-Cr/**K**= Rr Subtract Rr...4 Answers · Education & Reference · 05/10/2009

Architects and engineers consider the

**K**-factor of a sprinkler head when designing a fire... the capacity of a sprinkler system. The**K**-factor is often stated in a manufacturer...4 Answers · Science & Mathematics · 25/04/2013

**k**^0.5 = 6 square the whole equation (**k**^0.5 = 6)^2**k**= 6^2**k**= 36 RainMaker nifty-rainmaker.blogspot.com/5 Answers · Science & Mathematics · 10/05/2010

Let

**K**be a convex subset of R^p and let x,y be in the closure of**K**. Then there exist sequences (x_n), (y_n) of points in**K**such that lim x_n = x and lim y_n = y. The line segment between x_n and y_n...2 Answers · Science & Mathematics · 20/01/2012

##### Ad

related to: K